Development of e-jobsheet of clutch system maintenance in vocational high school - Akhmad, Akhmad; Setuju, Setuju; Hadi, Samsul; Gunawan, Teddy Surya (Universitas Sarjanawiyata Tamansiswa, 2024)
Abstract. This study aims to develop class XII clutch system maintenance e-jobsheet media at SMK Tamansiswa Jetis Yogyakarta and find out the feasibility of learning media E-jobsheet clutch system maintenance in PSPTKR subjects. This research uses 4D research. Namely define (denifisian), design (design), devolep (development) disseminate (dissemination ). with the data sources of this research are (1) Material Expert validators, (2) Media Experts, and (3) Learners. Data collection method using Observation and Questionnaire. Data analysis of this study uses qualitative descriptive techniques and uses a percentage scale, namely calculations in data analysis will produce percentages. The percentage calculation process is carried out by the number of values obtained and divided by the maximum score then multiplied by one hundred percent. The results showed that the feasibility level of material validation obtained a score of 85% in the very feasible category, media validation obtained a score of 88.75% in the very feasible category, small-scale product trials in students obtained a score of 79% in the very feasible category, and large-scale trials obtained a score of 81% in the feasible category. Keywords: Development, E-jobsheet, Learning, Coupling System,